Language Teaching Through The "Black Screen": Implications of an Emergency Remote Teaching Context in Higher Education - Christoforou, Maria (My University, 2021)
The COVID-19 pandemic has reshaped the experience of language teaching and learning in a radical way. Instructors are faced with the challenge of carrying out online lessons exclusively, re-designing teaching materials and making urgent use of new technological tools in order to establish a flow transition. However, the current conditions of the pandemic have officially "legitimised" a new type of teaching in a mandatory and imperative way, that of emergency distance teaching in an online environment. This pilot study explores the views of five language teachers in Higher Education (HE) on how their teaching practices changed in the context of remote learning in the fall semester of 2020. The study aims to explore the following two research questions: 1. which student language skill has been most affected in distance emergency teaching in an online environment, according to the teachers 2. to what extent language learning is pedagogically achieved in distance emergency teaching in an online environment. For data collection, semi-structured interviews are conducted individually, from which issues related to the shifting of language learning pedagogy in an emergency remote teaching in an online environment are elicited. Analysis brings to light the "black screen" phenomenon, which refers to the black screen of the videoconferencing software tool through which lessons take place, and the students’ tendency to “hide” behind the screen during the online lessons. Moreover, data analysis showed that writing is the most-affected skill under the new circumstances, as teachers are no longer able to detect their students' weaknesses. One of the issues brought to light by this study is that further empirical research, based on the views of students and more teachers, is needed to evaluate more fully the conditions of emergency remote language teaching in an online environment.
Keywords: Emergency Remote Language Teaching; Higher Education; Multimodality; E-learning